Mongolian Labor Migration to Republic of Korea in Recent Historical Period: Forced Mobility and Social Event - I. G. Aktamov; Yu. G. Grigoreva (Научный диалог)
The issues of the reasons, factors and features of labor migration of Mongolian citizens to the Republic of Korea in the post-socialist period of the country’s development are considered. The results of a comparative analysis of the data of official statistics, government bodies of Mongolia and the Republic of Korea, as well as international organizations are presented. A review of scientific works on this issue by domestic, Mongolian, South Korean authors is carried out. The relevance of the study is due to the need to analyze migration processes, which in the near future will determine the socio-economic development of the states of Northeast Asia, taking into account the age, professional, gender characteristics of the “receiving” and “arriving” communities. It has been proven that the government of Mongolia pays great attention to migration policy, which emphasizes the migration of Mongolian citizens to the Republic of Korea. The authors identified the main factors influencing migration flows, and also determined the mechanisms of state regulation in the recent historical period. In the conclusion, the results of the analysis carried out on the problem and the prospects for the development of the study are formulated, including in the field of studying migration flows from the border regions of the Russian Federation.